How does climate exacerbate root causes of conflict in Sudan? An impact pathway analysis - Dutta Gupta, Tanaya; Madurga Lopez, Ignacio M.; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Sudan, using an impact pathway analysis. Two main impact pathways are identified: 1) Resource availability and access pathway ; 2) Weak state capacity, resource governance and maladaptation pathways.